2010
DOI: 10.1007/s00210-010-0584-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the PKC inhibitors chelerythrine and bisindolylmaleimide I (GF 109203X) on delayed rectifier K+ currents

Abstract: PKC inhibitors are useful tools for studying PKC-dependent regulation of ion channels.For this purpose high PKC specificity is a basic requirement excluding any direct interaction between the PKC inhibitor and the ion channel. In the present study the effects of two frequently applied PKC inhibitors, chelerythine and bisindolylmaleimide I, were studied on the rapid and slow components of the delayed rectifier K + current (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PMA treatment augmentation of hNav1.7 resurgent current amplitude was prevented by pretreatment with the PKC antagonists Bis I or chelerythrine at the concentration of 1 lM (Fig. 1) [23,10]. In addition, 1 lM PMA also significantly shifted the peak voltage, the voltage where peak resurgent current was measured (from À39 mV for control to À33 mV for PMA treated; Suppl.…”
Section: Resultsmentioning
confidence: 90%
“…PMA treatment augmentation of hNav1.7 resurgent current amplitude was prevented by pretreatment with the PKC antagonists Bis I or chelerythrine at the concentration of 1 lM (Fig. 1) [23,10]. In addition, 1 lM PMA also significantly shifted the peak voltage, the voltage where peak resurgent current was measured (from À39 mV for control to À33 mV for PMA treated; Suppl.…”
Section: Resultsmentioning
confidence: 90%
“…The structural similarity between bisindolylmaleimides, chelerythine and staurospoorine suggested that bisindolylmaleimides may be a competitive inhibitor with respect to ATP. The inhibition of PKC by bisindolylmaleimides was demonstrated to be highly dependent on the ATP concentration [4,29]. GF 109203X inhibited collagenand alpha-thrombin-induced platelet aggregation as well as collagen-triggered ATP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of hERG as an antitarget, surprisingly few natural products have been tested for hERG channel blocking properties. A number of structurally diverse natural products have been shown to diminish hERG channel activity in vitro, e.g., naringenin, trimethyl-apigenin, curcumin, lobeline, chelerythrine, papaverine, and capsaicin [12][13][14][15][16][17][18]. It has been shown that the consumption of 1 L of freshly squeezed pink grapefruit juice (containing the hERG channel blocking flavanone naringenin) leads to a mild prolongation of the QTc interval in both young healthy volunteers and patients suffering from cardiomyopathy [12,19].…”
Section: Abbreviationsmentioning
confidence: 99%